An Investigation of the Risk Factors for Dental Caries After Head and Neck Radiotherapy - Katsura, Kouji; Kobayashi, Taichi; Takamura, Masaki; Tanaka, Keiko; Ishiyama, Mayuka; Kurokawa, Akira; Soga, Marie; Niimi, Kanae; Hayashi, Takafumi (Shika Hoshasen, 2022)
Background and Purpose: Dental caries that arise after radiotherapy （radiation caries） can lead to reduced masticatory function caused by tooth loss and osteoradionecrosis caused by dental infections. There are two main opinions regarding the mechanism underlying radiation caries: 1） tooth fragility caused by the direct effects of radiation and 2） a reduction in the physiological effects of saliva due to hyposalivation and a worsening of oral status. However, it has not been clarified which of these mechanisms is the main cause of radiation caries. Therefore, the purpose of this study was to investigate the risk factors for radiation caries in patients who had received head and neck radiotherapy. 　Material and Methods: Forty patients who had received head and neck radiotherapy were enrolled. We retrospectively investigated the relationships between radiation caries and clinical parameters, such as the treated site, irradiation field, radiation dose, and oral status, for 3 years after the completion of radiotherapy. 　Results: The incidence rate of radiation caries was 85％. Twenty-two percent and 78％ of radiation caries occurred within and outside the irradiation field, respectively. The incidence rate of radiation caries among teeth within and outside the radiation field was 41.7％ and 57.7％, respectively. The occurrence of radiation caries showed a moderate positive correlation with plaque control records. On the other hand, it was not correlated with the total radiation dose, the mean radiation dose delivered to the parotid gland, or the amount of saliva. 　Discussion: Our results suggested that radiation caries occur both within and outside the radiation field. It is considered that the risk of radiation caries is affected more by oral status, such as poor oral hygiene, than structural changes in teeth caused by radiation. Therefore, it is important to maintain a good oral status after head and neck radiotherapy to prevent radiation caries.